Photovoice and Photo-Elicitation in Management Education. (September 2019) - Trott, David; Tomsett, Paula May; Shaw, Michael
In this article, we show that "photovoice" and "photo-elicitation" are user-friendly, versatile techniques uniquely beneficial in International Business programs where English-mediated instruction is the norm. These techniques engage young adult students deeply in subject material as well as create the opportunity for students to develop extemporaneous or impromptu English speaking skills. Photovoice and photo-elicitation lend themselves to being quintessential andragogy-in-action: learner-directed not teacher-directed, use of dialogue instead of monologue, and focus on student outcome choices instead of teacher-programmed assignments. They foster high interactivity not passive (silent) absorption in the teaching/learning process and stimulate cocreation of diverse meanings, interpretations, and imaginations. Course content is made relevant and reinforced as students are helped to find, share, and value their own personal empowering and authentic "voice"—in English.